2014
DOI: 10.1093/molehr/gau028
|View full text |Cite
|
Sign up to set email alerts
|

Single- and double-stranded viral RNA generate distinct cytokine and antiviral responses in human fetal membranes

Abstract: There has been growing interest in the role of viral infections and their association with adverse pregnancy outcomes. However, little is known about the impact viral infections have on the fetal membranes (FM). Toll-like receptors (TLR) are thought to play a role in infection-associated inflammation at the maternal-fetal interface. Therefore, the objective of this study was to characterize the cytokine profile and antiviral response in human FMs exposed to viral dsRNA, which activates TLR3, and viral ssRNA, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 82 publications
(116 reference statements)
1
40
0
Order By: Relevance
“…Furthermore, we have previously shown using siRNA studies that engagement of TLR2 and TLR5 enhances production of cytokines and MMP-9 in fetal membranes [22]. In vitro studies have also shown that bacterial products such as LPS and flagellin, and the viral dsRNA analogue poly(I:C), stimulate pro-inflammatory cytokines in fetal membranes [22,27,58]. Thus, we used LPS, flagellin and poly(I:C) to mimic infection-induced preterm birth in vitro to assess the importance of AMPK in regulating pro-inflammatory cytokines in fetal membranes.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we have previously shown using siRNA studies that engagement of TLR2 and TLR5 enhances production of cytokines and MMP-9 in fetal membranes [22]. In vitro studies have also shown that bacterial products such as LPS and flagellin, and the viral dsRNA analogue poly(I:C), stimulate pro-inflammatory cytokines in fetal membranes [22,27,58]. Thus, we used LPS, flagellin and poly(I:C) to mimic infection-induced preterm birth in vitro to assess the importance of AMPK in regulating pro-inflammatory cytokines in fetal membranes.…”
Section: Discussionmentioning
confidence: 97%
“…Associations between viral infections and chorioamnionitis and/or spontaneous preterm birth have been also reported (Gomez et al 2008, Tsekoura et al 2010. Furthermore, the viral dsRNA analogue poly(I:C) induces pro-inflammatory cytokines in foetal membranes (Bakaysa et al 2014). It was thus of interest to determine if KLF5 regulates pro-inflammatory and pro-labour mediators in the presence of IL1b, flagellin and the poly(I:C) in human myometrium.…”
Section: Discussionmentioning
confidence: 98%
“…NFkB has been shown to regulate the expression of numerous pro-labour genes including IL6, IL8 and COX2 in the presence of infection or inflammation (Belt et al 1999, Lappas et al 2002, 2003, Lappas & Rice 2007, Bakaysa et al 2014. Studies in non-gestational tissues demonstrate that NFkB is required for KLF5 signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from the trophoblast cell lines and mouse placental tissue was extracted using TRIzol, chloroform, and 2-propanol according to the manufacturer's instructions (Life Technologies) as previously described [35,36]. Total RNA concentrations were measured at A260 using a NanoDrop (Thermo Scientific) and stored at À808C.…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%
“…Total RNA concentrations were measured at A260 using a NanoDrop (Thermo Scientific) and stored at À808C. For the analysis of mRNA expression levels, quantitative real-time PCR (qPCR) was performed using the KAPA SYBR FAST qPCR kit (Kapa Biosystems) on the Bio-Rad CFX Connect Real-Time System (Bio-Rad) as previously described [35][36][37]. All primer sequences used are shown in Table 1.…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%